Preparation of multi-walled carbon nanotubes/high density polyethylene composites with enhanced properties by using a master batch method. Issue 9 (November 2021) - He, Fu-An; Zhang, Li-Ming
Multi-walled carbon nanotubes (MWCNTs)/high density polyethylene (HDPE) composites were prepared by a masterbatch method (mPEC) in which a commercial HDPE was blended with a MWCNTs/HDPE masterbatch obtained from in situ polymerization. Owing to the interfacial interaction, a 13 cm −1 up-shift of the G band for the MWCNTs was observed in the Raman spectrum of the MWCNTs/HDPE masterbatch and the homogeneous distribution of MWCNTs in the mPEC was realized. Compared to the pure HDPE and the MWCNTs/HDPE composites prepared by a direct melt-blending method (dPEC), the mPEC had better electrical, mechanical and rheological properties, suggesting that the in situ polymerized HDPE covering on the MWCNTs surfaces played an important role in the reinforcing effects as an interfacial modifier. The tensile yield strength and the Young's modulus of the mPEC containing 3 wt% MWCNTs (mPEC3), and the flexural strength and the flexural modulus of the mPEC containing 1 wt% MWCNTs were improved by 38.3%, 41.7%, 24.4%, and 42.9%, respectively, compared to those of the pure HDPE. For, the electrical resistivity of mPEC3 was decreased by about three orders of magnitude relative to that of the pure HDPE. The | η *|, G′, and G″ of the mPEC were obviously higher than those of pure HDPE. Moreover, the polyethylene-modified MWCNTs obtained from in situ polymerization could facilitate the crystallization of the HDPE macromolecular chains more effectively compared to the unmodified MWCNTs.